Revision of the Embolemidae of Japan (Hymenoptera: Chrysidoidea), with description of a new genus and two new species - Olmi, Massimo; Mita, Toshiharu; Guglielmino, Adalgisa (Zootaxa, 2014)
Seven species of Embolemidae are recognized in Japan. They belong to two genera: Embolemus Westwood 1833 and Trogloembolemus Olmi, Mita et Guglielmino, gen. nov. (type species T. fujiei Olmi, Mita et Guglielmino, sp. nov.) Embolemus honshuensis Olmi, Mita et Guglielmino, sp. nov. (Japan, Honshu) and Trogloembolemus fujiei Olmi, Mita & Guglielmino, sp. nov. (Japan, Honshu) are described and figured. A key to the genera and species of Japan is presented. Trogloembolemus fujiei sp. nov., collected in the soil at a depth of two metres and almost blind, is the first species of Embolemidae with troglobitic habitus.